The integrals in Gradshteyn and Ryzhik. Part 29: Chebyshev polynomials - Victor H. Moll; Christophe Vignat (Scientia Series A: Mathematical Sciences, 2025)
The table of Gradshteyn and Ryzhik contains many integrals that involve Chebyshev polynomials. Some examples are discussed.
Keywords: Integrals; Chebyshev polynomials.